حلِ مختلف الحدیث میں سید احمد حسن کا منہج و اسلوب : احسن التفاسیر کا خصوصی مطالعہ: Syed Ahmad Hasan's Methodology in Harmonizing the Contradictory Ḥadith Narrations: A Study of Aḥsan al-Tafāsīr (Al-Qamar, 2021)
Syed Ahmad Hassan is a renowned Exegete of the 20th century as well as an expert in hadith and its sciences. His Tafseer "Ahsan-ul-Tafaseer" enjoys very prominent place among the Tafseeri literature of sub-continent. . This book is not only the main source of interpretation and understanding of the Quran, but the author has combined many sciences in it, one of them  is the knowledge of resolving conflicts of (Mukhtalful Hadees). The need for solve the conflict actually arises when the meanings of two sahih hadiths seems to be opposite each other . In such case, resolving the clash is called Raf` e Ta`arud. The fact is that the contradiction between the shar'i arguments or two different hadiths is only apparent, not real, because it is not possible for two hadiths from the Prophet (PBUH) to be authentic and contradictory. However, In "Ahsan-ul-Tafaseer"has also arranged for the resolution of contradictions.
Keywords: Ta`rud; Ikhtilaf; Mukhtalful Hadith; Naskh; Tarjeeh; Jam` o Taber